Digital Marketing: Marketing Strategy for Madrasah Education Services During The Covid-19 Pandemic - Arifin, Zainal; Artanto, Dicky; Rahman, Ainur (JURNAL AL-TANZIM, 2023)
This study aims to analyze marketing strategies to promote madrasas for new students. The research approach is descriptive qualitative to analyze the digital marketing process that madrasas have carried out in recruiting new students during the Covid-19 pandemic. Data analysis was carried out interactively using the Miles and Huberman method, which included data collection, data presentation, data reduction, and concluding. The study results show that, first, the "superior madrasah" brand is part of digital marketing carried out by MTs N 1 Yogyakarta to attract new students. Second, the digital marketing process is carried out through several stages: setting goals, mapping target markets, initiating and planning content, creating content, distributing content, strengthening content, evaluating content marketing, improving content marketing, and online and offline marketing. Third, digital marketing is quite effective in increasing the enrollment of new students at madrasah.